2018
DOI: 10.1002/jemt.23171
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol treatment of spinal cord injury in rat model

Abstract: Spinal cord injury (SCI) is catastrophic and can culminate in disability and death. The routine therapy employed in early stages of SCI currently entails surgical procedures combined with high doses of methylprednisolone (MP). MP is highly controversial for the lack of consensus on its true therapeutic effects. Resveratrol (RES) has recently been recognized as a potential and novel therapeutic drug in SCI. Herein, we investigated the effect of RES in a SCI rat‐model and found significant improvement in Basso–B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Resveratrol has been proved to be beneficial in a broad type of pathological conditions including tumor, myocardial ischemia reperfusion injury, and oxidative stress [ 16 ]. Previous study indicated that resveratrol protected against SCI via activating autophagy and inhibiting apoptosis through SIRT1/AMPK [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol has been proved to be beneficial in a broad type of pathological conditions including tumor, myocardial ischemia reperfusion injury, and oxidative stress [ 16 ]. Previous study indicated that resveratrol protected against SCI via activating autophagy and inhibiting apoptosis through SIRT1/AMPK [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the group SCI+resveratrol, 30 mg/kg of resveratrol was injected intraperitoneally daily for the first 14 days after SCI. In the group SCI+resveratrol+XAV939, 0.5 mg/kg of XAV939 and 30 mg/kg of resveratrol were injected intraperitoneally daily for the first 14 days after SCI [ 11 , 16 ]. Same amount of saline was injected in the group sham and SCI.…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol also blocks the Notch signaling pathway to limit SCI [212]. Liu et al reported that resveratrol was an effective treatment for SCI by reducing neuronal cell apoptosis and inflammation [213]. In a recent study by Song et al, 10 mg/kg of resveratrol and puerarin-loaded nanoparticles attenuated CAT, SOD, and GSH antioxidant levels [214].…”
Section: Caffeic Acid Phenethylmentioning
confidence: 99%
“…TGF-activated kinase 1 is closely linked with the MAPK and NF-κB signaling. Activated TAK1 can accelerate the MAPK and NF-κB signaling pathways and resveratrol attenuates the inflammation by the inhibition of TAK1 activity [21,22].…”
Section: Discussionmentioning
confidence: 99%